Research Trends on Digital Learning in Science Education: Bibliometric Analysis - Ester Elinawati Waruwu; Muktiningsih Nurjayadi; Sukro Muhab; Irwanto Irwanto; Firas Tayseer Ayasrah (Jurnal Pendidikan Sains Indonesia, 2026)
Digital learning has become one of the rapidly growing research areas in science education. However, the knowledge structure, patterns of scientific collaboration, and thematic development of research in this field have not yet been comprehensively mapped. This study aims to identify publication trends, collaboration networks, influential contributors, and the thematic structure of research on digital learning in science education. Data were collected from the Scopus database using predefined search criteria, resulting in 523 journal articles published between 1999 and 2025. Bibliometric performance analysis and science mapping were conducted using Bibliometrix (R-package) and VOSviewer. The results indicate that publications on digital learning in science education have grown significantly, particularly after 2020, accompanied by an increase in international research collaboration. The analysis also identified the countries, institutions, authors, and journals that have played significant roles in the development of this field. Furthermore, keyword analysis revealed that e-learning, students, and science education constitute the core research themes, while temporal analysis demonstrated a shift in research focus from web-based learning and distance education toward more interactive learning technologies, such as educational technology, augmented reality, and virtual reality. These findings indicate that digital learning in science education has evolved into an increasingly mature, collaborative, and technology-oriented research field, emphasizing the use of digital technologies to enhance the quality of instruction and students' learning experiences